Industrial training report: Department of Teknologi Maklumat Unit Governance Lembaga Tabung Haji Tun Razak / Norerryanie Mokhtar - Mokhtar, Norerryanie (Perpustakaan Tengku Anis, 2017)
This report describes the activities of the trainee during industrial training for a period offtve(5) months. Based on the period.from 1 August until 31 December 2017 at Lembaga Tabung Haji headquarters (Jalan Tun Razak, Kuala Lumpur), the trainee has been exposed with the real working environment and it is totally different with study environment at the campus. It has given the trainee to feel the experience in a working environment at the campus. Throughout the training period, the trainee had gathered many experience such as handling administrative task, managing records and involving in preparing the documentation of policies and procedures. The trainee has completed a project, which is a compilation of 'Dasar ICT Tabung Haji' through infographic form. It was a valuable opportunity for the trainee to get familiar with real working environment.